Motivation in medical students: a PhD thesis report - Kusurkar, Rashmi (Bohn Stafleu van Loghum, 2012)
The aims of this thesis were to gather insights and investigate the factors influencing, outcomes and applications of medical students' motivation. This thesis consists of three literature reviews, four research papers and two application papers. Two research studies investigated the relationships of student motivation with study strategy, effort and academic performance through structural equation modelling and cluster analysis. The relationships of age, maturity, gender and educational background with motivation were investigated through multiple regression analysis. The results of this thesis were 1. Developments in medical education appear to have undervalued student motivation. 2. Motivation is an independent variable in medical education; intrinsic motivation is significantly associated with deep study strategy, high study effort and good academic performance. 3. Motivation is a dependent variable in medical education and is significantly affected by age, maturity, gender, educational background; intrinsic motivation is enhanced by providing students with autonomy, feedback and emotional support. 4. Strength of motivation for medical school can be reliably measured by Strength of Motivation for Medical School questionnaire. The conclusion of this thesis was that it is important to give consideration to motivation in medical education because intrinsic motivation leads to better learning and performance and it can be enhanced through giving students autonomy in learning, feedback about competence and emotional support.